Penggunaan Konjungsi pada Tesis Mahasiswa Program Studi Pendidikan Matematika dan Pendidikan Bahasa, Kekhususan Pendidikan Bahasa Indonesia Pps Universitas Negeri Makassar - Basri Basri (SOCIETIES: Journal of Social Sciences and Humanities, 2021)
Abstract. This type of research is a qualitative descriptive study using the analysis model of Miles and Huberman. The data source in this study was the student's thesis of the Mathematics Education and Language Education Study Program, the specialization of Indonesian Language Education PPs, Makassar State University. The data collection techniques in this study were documentation, read-reading, recording / understanding, and data classification. The results showed that (1) all types and forms of conjunctions were used in the student thesis of the PPs Mathematics Education Study Program, Makassar State University. (2) all types and forms of conjunctions are used in the thesis of students of the Language Education Study Program, the specificity of Indonesian Language Education PPs Makassar State University. (3) variations in the use of conjunctions in the Mathematics Education Study Program students' theses include errors in using subordinate conjunctions, use of coordinative conjunctions, use of correlative conjunctions, and conjunctions between sentences. (4) variations in the use of conjunctions in the student thesis of the Language Education Education Study Program, the specificity of Indonesian Language Education PPs Makassar State University includes errors in using subordinate conjunctions, coordinative conjunctions, correlative conjunctions, and conjunctions between sentences. (5) the comparison of the misuse of conjunctions in the thesis of students of the Mathematics Education Study Program and the Language Education Study Program, the specificity of Indonesian Language Education PPs Makassar State University shows that the misuse of conjunctions in the thesis is more dominated by students of the PPs Mathematics Education Study Program, Makassar State University. Keywords: conjunctions, variations, errors, and comparisons